Estimation of minimum wage in the aspect of preservation human capital - Renkas, Jurij (SPC Journal of Education, 2020)
The article presents an overview of the basic models of measuring the value of human capital, which are based on the theory of labor economics. There is also a systematic study of economic constant, which is an integral part of the capital model. An empirical study was presented, which found that economic constant of potential growth was at the level of 0.08 [1/year]. The calculation of the minimum wage for the economy of Ukraine in the light of the theory of measuring the value of human capital is also presented. The percentage of compliance with the statutory and theoretically calculated wages has been calculated. The data obtained are compared with the results of calculations of this indicator for the economy of the USA and Poland. Comparable percentages of minimum wage compliance can be used to build appropriate country ratings.